The Role of Work Motivation in Mediating The Work Environment on Employee Performance CV. Arafa Power Abadi Yogyakarta - Saputra, Sandi; Utami, Esti Margiyanti; Annisa, Nenden Nur (CV ODIS, 2024)
Human resources in a company must be managed professionally to create a balance between employee needs and the demands and capabilities of the company's organization. The company expects effective performance so that it obtains good work results in terms of quality and quantity through the responsibilities given to employees. Employee performance relates to several aspects such as work environment and motivation. The purpose of this research is to test the influence of the work environment on employee performance, test the influence of the work environment on work motivation, test the influence of work motivation on employee performance, and test the influence of the work environment on employee performance with work motivation as a mediating variable. The population in this study were CV employees. Arafa Power Abadi, Yogyakarta. The sampling technique in this research used saturated samples and a sample of 80 respondents was obtained. The data collection instrument uses a questionnaire and answers are assessed using a Likert scale. A validity and reliability test was first carried out to determine the measurements' accuracy and the questionnaire parameters' stability. Data analysis using the SmartPLS 3.0 for Windows tool. This research shows that the work environment has a positive effect on employee performance, work motivation has a positive effect on employee performance, and work motivation mediates the effect of the work environment on employee performance.